A safer and more practical tracheotomy in invasive mechanical ventilated patients with COVID-19: A quality improvement study - Kang, Kai; Wang, Junfeng; Du, Xue; Li, Nana; Jin, Songgen; Ji, Yuanyuan; Liu, Xinjia; Chen, Pengfei; Yue, Chuangshi; Wu, Jihan; Wang, Xintong; Tang, Yujia; et al. (Frontiers in Surgery, 2022)
Importance: The number of infections and deaths caused by the global epidemic of severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) invasion is steadily increasing daily. In the early stages of outbreak, approximately 15% to 20% of patients with coronavirus disease 2019 (COVID-19) inevitably developed severe and critically ill forms of the disease, especially elderly patients and those with several or serious comorbidities. These more severe forms of disease mainly manifest as dyspnea, reduced blood oxygen saturation, severe pneumonia, acute respiratory distress syndrome (ARDS), thus requiring prolonged advanced respiratory support, including high-flow nasal cannula (HFNC), non-invasive mechanical ventilation (NIMV), and invasive mechanical ventilation (IMV). Objective: This study aimed to propose a safer and more practical tracheotomy in invasive mechanical ventilated patients with COVID-19. Design: This is a single center technological improvements study. Setting: Single central study. Participants: Tracheotomy is a necessary and important step in airway management for COVID-19 patients with prolonged endotracheal intubation, IMV, failed extubation, and ventilator dependence. Standardized third-level protection measures and bulky personal protective equipment (PPE) may hugely impede the implementation of tracheotomy, especially when determining the optimal pre-surgical positioning for COVID-19 patients with the ambiguous surface position, obesity, short neck or limited neck extension, due to vision impairment, reduced tactile sensation and motility associated with PPE. Consequently, the aim of this study was to propose a safer and more practical tracheotomy, namely percutaneous dilated tracheotomy (PDT) with delayed endotracheal intubation withdrawal under the guidance of bedside ultrasonography without the conventional use of flexible fiberoptic bronchoscopy (FFB), which can accurately determine the optimal pre-surgical positioning, as well as avoid intraoperative damage of the posterior tracheal wall and prevent the occurrence of tracheoesophageal fistula (TEF).